Kassetekstens didaktikk. Korte prosatekster i klasserom og auditorium - Auklend, Morten (Nordlit, 2022)
When teaching literature to high school or college pupils, or university students—i.e., inexperienced readers—there are great benefits in using shorter prose texts, so-called «box-texts». The practical short format of flash fiction, short prose, and prose lyric is already known, and the everyday experience from using brevity when writing and reading e-mails, news stories, mobile texts, telling anecdotes and jokes, and life in social media in general will inform and guide untrained readers of literature. By focusing on an already known (but not internalized) format and the economy of language therein and highlighting the format as a didactive resource in its own right, teachers of literature can more easily educate pupils and students with the knowledge that certain ways of thinking about aesthetics, form(at) and language are familiar to readers, who will nevertheless need theorizing and teaching.
Keywords: literary didactic; curriculum; contextual collapse; literacy; boxed-texts